DIGITAL HUMAN RIGHTS PROTECTION: LEGAL TRANSPLANTATION STRATEGIES TO REALIZE SUSTAINABLE DEVELOPMENT IN INDONESIA’S DIGITALIZATION ERA - Khofidhotur Rovida; Sasmini Sasmini (Domus Legalis Cogitatio, 2024)
The advancement of information and communication technology brings great benefits to society, such as ease of communication and access to public services. However, technology also threatens human rights, including privacy and freedom of expression. This study aims to analyze the legal strategies of other countries to protect digital human rights that can be applied in Indonesia, as well as formulate policies to improve this protection through legal transplantation and support sustainable development goals. The method is normative legal research, with data from related laws and policies. The results of this study indicate that the adoption of rules is a potential strategy to improve the security of digital human rights in Indonesia and provide greater control over the personal data of individuals. The implementation of the General Data Protection Regulation (GDPR) in Indonesia is considered important to align personal data protection with international standards, improve the country's reputation, and facilitate international cooperation. With clear regulations, public trust in digital services will increase, because people feel safer and more protected from misuse of personal data. This stricter legal framework helps create a safer and more inclusive digital environment so that all levels of society can actively participate in the digital economy.